Effect of Fennel Extract on the Improvement of Memory Disorders in Beta Amyloid Alzheimer Model of Male Wistar Rats - Delaram Eslimi Esfehani; Shahrbanoo Oryan; Maryam Khosravi; Farhad Valizadegan (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2019)
Introduction: Alzheimer's disease is the most common neurodegenerative disorder. Due to the neurodegenerative effect of fennel (Foeniculum vulgare) this study aimed at investigating the effect of this plant on the improvement of learning and memory in rat models of Alzheimer's disease.